Small bowel intussusception secondary to inverted Meckel's diverticulum - Wesley E. Barry, III; David M. Rosenberg; Mikako Warren; Eugene S. Kim (Elsevier, 2017)
Meckel's diverticula are common congenital gastrointestinal malformations that most often present with bloody stool or bowel obstruction. Occasionally these diverticula may become inverted and serve as a lead point for the development of intussusception. Herein, we report the case of a 10-year old female presenting with abdominal pain and non-bloody, non-bilious emesis and suspicion of intussusception. Upon performing an exploratory laparotomy, the intussusception lead point was found to be an inverted Meckel's diverticulum obstructing the lumen of the intestine.